Velar o tempo: vivências em pintura e areia colorida - Siebra, Paula Freire (2025)
This research aims to investigate the creative processes related to artistic experimentation involving painting and colored sand bottles (silicography) produced in territories of the coast of Ceará, based on works created by the author herself and by colored sand artists living in the village of Majorlândia. Musing on the formal implications, poetic reverberations and social, market and institutional tensions that permeate both practices, the dissertation is based on essay writing and field experience reports to investigate how the interaction of painting and silicography proposes new poetic possibilities for the notion of landscape representation, exploring intersections between the savoir-faire of both practices and tensioning their regimes of visibility. Some of the references are: Gaston Bachelard (2019), Fayga Ostrower (2001), Sally Price (1991), Octavio Paz (1983), Jacques Rancière (2009), and many others.